2019
DOI: 10.3390/ma12203329
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Geometry Parameters of Inkjet-Printed Silver Nanoparticle Traces on PDMS Substrates Using Response Surface Methodology

Abstract: Inkjet printing is an emerging technology with key advantages that make it suitable for the fabrication of stretchable circuits. Specifically, this process is cost-effective and less complex compared to conventional fabrication technologies. Inkjet printing has several process and geometry parameters that significantly affect the electromechanical properties of the printed circuits. This study aims to optimize the geometry parameters of inkjet-printed silver nanoparticle traces on plasma-treated polydimethylsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The RSM design technique is commonly in use these day because of its design performance and exemption of cost [4,[23][24][25][26]. The ultimate goal of RSM is to examine the region of factor space where operating requirements are satisfied [27][28][29]. The RSM technique was used in the current study to consider pouring temperature, pouring velocity and moisture content as input variables.…”
Section: Methodsmentioning
confidence: 99%
“…The RSM design technique is commonly in use these day because of its design performance and exemption of cost [4,[23][24][25][26]. The ultimate goal of RSM is to examine the region of factor space where operating requirements are satisfied [27][28][29]. The RSM technique was used in the current study to consider pouring temperature, pouring velocity and moisture content as input variables.…”
Section: Methodsmentioning
confidence: 99%
“…The method was further optimized by Žlebič et al [201], testing different Ag nanoparticle inks. Abu-Khalaf et al [202] reported enhanced geometrical parameters of the inkjet-printed Ag nanoparticle traces on plasma-treated PDMS substrates. Zhang et al [203] performed a comparative study of the parameters of two sensors: sensors made by the inkjet technique and sensors made by the screen-printing technique.…”
Section: Strain/pressure Sensorsmentioning
confidence: 99%
“…Inkjet printing (IJP) is a promising technology in the fabrication of stretchable and wearable sensors. Compared with other fabrication techniques, IJP has less sophisticated process and lower cost [18][19][20][21]. The IJP RR sensor was fabricated on polydimethylsiloxane (PDMS) substrate using conductive silver nanoparticle ink, as shown in Figure 1a which was presented in [22].…”
Section: Sensorsmentioning
confidence: 99%